Does the Board of Directors' Concern for the Environment Affect Financial Performance? - Mediaty Mediaty; Wahyudi Wahyudi; Abdul Hamid Habbe (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research explores the impact of board of directors' environmental concerns on financial performance. This is the first examination of how board characteristics, focusing on environmental performance as an intervening factor, affect financial performance. This study specifically considers the context of the Indonesian capital market. The level of environmental concern is assessed by examining the characteristics and background of the board of directors with respect to environmental considerations. Multiple regression analysis methods are used to explore relationships between variables. This study used samples and data from companies listed on the Indonesia Stock Exchange during the period 2020 to 2022. The findings showed that the board's emphasis on environmental issues did not produce a statistically significant impact on the company's financial performance.